2010
DOI: 10.2478/v10078-010-0027-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Whole Body Vibration on Shoulder Muscular Strength and Joint Position Sense

Abstract: Acute Effects of Whole Body Vibration on Shoulder Muscular Strength and Joint Position Sense Functional changes following whole body vibration (WBV) training have been attributed to adaptations in the neuromuscular system. However, these changes have mainly been observed in the lower extremity with minimal change to the upper extremity. The purpose of the study is to examine the acute effect of shoulder vibration on joint position sense and selected muscle performance characteristics (peak torqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 35 publications
1
25
0
3
Order By: Relevance
“…Our study is in agreement with the previous studies that also found an increase of EMG activity during WBV over upper limb muscles (8,9,11,15) confirming that WBV is an effective tool to increase the muscular activity of upper limb. This study has shown that WBV is also effective in distinct subjects other than healthy, who have been the focus of studies until this point.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study is in agreement with the previous studies that also found an increase of EMG activity during WBV over upper limb muscles (8,9,11,15) confirming that WBV is an effective tool to increase the muscular activity of upper limb. This study has shown that WBV is also effective in distinct subjects other than healthy, who have been the focus of studies until this point.…”
Section: Discussionsupporting
confidence: 93%
“…WBV applied over upper limbs has increased the muscular performance and EMG activity in a healthy population (8)(9)(10)(11)15).…”
Section: Introductionmentioning
confidence: 99%
“…This caused an imbalance in the shoulder muscles and even caused pain14 ) . According to a study by Hong et al15 ) , the torque of motion in shoulder joints significantly increased after vibrations were applied their subjects via a vibration platform. According to a study by Kirkesola16 ) , when a sling was used for vibration exercise, it was found that incorrect neuromuscular control could be corrected, thereby reducing muscle imbalance.…”
Section: Discussionmentioning
confidence: 99%
“…Controlling the range of motion and muscle tension, and limiting the arc of joint motion, aimed at preventing injuries, is mostly due to the action of the nervous system. Proprioception in this system may be associated with joints or muscles [12].…”
Section: Proprioception Mechanismsmentioning
confidence: 99%